2008
DOI: 10.1086/533492
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Magnetic Field Geometry on the Evolution of Black Hole Accretion Flows: Similar Disks, Drastically Different Jets

Abstract: Because the magnetorotational instability is capable of exponentially amplifying weak preexisting magnetic fields, it might be hoped that the character of the magnetic field in accretion disks would be independent of the nature of the seed field. However, the divergence-free nature of magnetic fields in highly conducting fluids ensures that their large-scale topology is preserved, no matter how greatly the field intensity is changed. By performing global two-dimensional and threedimensional general relativisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
307
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(332 citation statements)
references
References 23 publications
24
307
0
1
Order By: Relevance
“…Unlike the simulations in De , , Hirose et al (2004), Krolik et al (2005), Hawley & Krolik (2006), Beckwith et al (2008), McKinney &Gammie (2004), andMcKinney (2005) that considered a finite toroidal pool of gas, threaded by poloidal loops of like orientation, Igumenshchev (2008) considered an endless supply of gas from the outer boundary. This is a major fundamental distinction from the poloidal loop simulations.…”
Section: A Fundamental Topological Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the simulations in De , , Hirose et al (2004), Krolik et al (2005), Hawley & Krolik (2006), Beckwith et al (2008), McKinney &Gammie (2004), andMcKinney (2005) that considered a finite toroidal pool of gas, threaded by poloidal loops of like orientation, Igumenshchev (2008) considered an endless supply of gas from the outer boundary. This is a major fundamental distinction from the poloidal loop simulations.…”
Section: A Fundamental Topological Issuementioning
confidence: 99%
“…As a corollary to this, it customarily concluded that the accretion disk cannot maintain a strong magnetosphere and therefore the jet power would be quite small relative to Fanaroff-Riley type II (FRII) radio sources (Ghosh & Abramowicz 1997). 5 The only place in which a strong field can exist in this scenario is pinned against the event horizon, in the vortex of the accretion flow, and then only under a select set of circumstances (Beckwith et al 2008). Conversely, the second scenario implies that large-scale poloidal magnetic fields can be maintained by the accreting gas all the way down to the black hole (Bisnovatyi-Kogan & Ruzmaikin 1974Narayan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, the RIAF model has progressed from a simple semianalytical model to more complex time-dependent generalrelativistic magnetohydrodynamic (GRMHD) models. In these models relativistic jets are often produced (e.g., Beckwith et al 2008). The synchrotron emission from a GRMHD-RIAF can now be calculated with a high degree of precision using general relativistic radiative-transfer codes (e.g., Dolence et al 2009;Dexter & Agol 2009;Shcherbakov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that GRMHD simulation results depend on the initial magnetic field strength and topology (Beckwith et al 2008;Penna et al 2010;Tchekhovskoy et al 2011;McKinney et al 2012). The rotation rate of the initial torus may also be important.…”
Section: Introductionmentioning
confidence: 99%